NOD1 Agonist Protects Against Lipopolysaccharide and D-Galactosamine-Induced Fatal Hepatitis Through the Upregulation of A20 Expression in Hepatocytes - Jia, Fang; Deng, Fuxue; Xu, Pan; Li, Shiying; Wang, Xuefu; Hu, Peng; Ren, Hong; Tong, Shiwen; Yin, Wenwei (Frontiers in Immunology, 2021)
Increasing evidence suggests that NODs are involved in liver diseases; however, the underlying mechanisms remain obscure. In the present study, we analyzed the effect of NOD1 agonist pretreatment on acute liver failure induced by lipopolysaccharide (LPS) in D-galactosamine (D-GalN)-sensitized mice. We found that pretreatment with the NOD1 agonist markedly reduced LPS/D-GalN-induced mortality, elevation of serum ALT levels and hepatocyte apoptosis. The protective effect of NOD1 agonist was independent of tumor necrosis factor (TNF)-α inhibition. NOD1 agonist pretreatment also attenuated TNF-α/D-GalN-induced apoptotic liver damage. The anti-apoptotic protein A20 expression was more pronounced in NOD1 agonist pretreated mice than in controls, and knockdown of A20 abrogated the protective effect of NOD1 agonist on LPS/D-GalN-induced liver injury and hepatocyte apoptosis. Further experiments showed that NOD1 agonist-induced A20 upregulation required the presence of Kupffer cells and TNF-α. Taken together, our data strongly indicate that NOD1 is involved in the regulation of liver injury and could be a potential therapeutic target for liver diseases.